2021
DOI: 10.29312/remexca.v12i3.2609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus sp. on soil chemical and microbiological attributes and development of soybean and maize

Abstract: Plant growth-promoting rhizobacteria (PGPR) inhabit the rhizosphere of several cultivated plants. Bacteria of the genus Bacillus have great functional importance in plant development. The objective of this research was to evaluate different doses of Bacillus sp. in the development of soybean and corn crops and in the chemical and microbiological attributes of the soil. The essays were conducted in the field in the 2016/2017 harvest. The soybean and corn seeds were treated with two doses of Bacillus sp. at a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The 10 7 -concentration obtained higher results than the 10 6 -concentration. João- Alves et al (2021) reported that, in a study with corn and soybean, increasing the concentration of the bacterial solution increased production. In conclusion, a higher concentration of CFUs in these strains is necessary to obtain better results.…”
Section: Strains Biochemical Testsmentioning
confidence: 99%
“…The 10 7 -concentration obtained higher results than the 10 6 -concentration. João- Alves et al (2021) reported that, in a study with corn and soybean, increasing the concentration of the bacterial solution increased production. In conclusion, a higher concentration of CFUs in these strains is necessary to obtain better results.…”
Section: Strains Biochemical Testsmentioning
confidence: 99%